Emerging manufacturers engagements in the COVID −19 vaccine research, development and supply - Pagliusi, Sonia (Vaccine, 2020)
The World Health Organization declared the COVID-19 disease as a pandemic requiring a rapid response. Through online search, direct communication with network members and an internal survey, engagements of developing countries’ vaccine manufacturers’ network members in the research and development of COVID-19 vaccines and their capacities in the manufacturing, fill-finish and distribution of vaccines were assessed. Currently, 19 network members engaged in research and development of COVID-19 vaccines, using six principal technology platforms. In addition, an internal survey showed that the number of vaccines supplied collectively by 37 members, in 2018–19, was about 3.5 billion doses annually. Almost a third of network members having vaccines prequalified by the World Health Organization comply with international regulations and mechanisms to distribute vaccines across borders. The use of existing manufacturing, fill-finish and distribution capabilities can support an efficient roll-out of vaccines against COVID-19, while maintaining supply security of existing vaccines for on-going immunization programmes.